Electrical conductivity in the mantle transition zone beneath eastern Central Asian Orogenic Belt revealed by geomagnetic signals - Zhang, Yanhui; Hu, Yujia; Ma, Mina; Zhang, Yuyan (Scientific reports, 2025)
In the eastern segment of the Central Asian Orogenic Belt (CAOB), there is widespread volcanic magma activity. However, there is still considerable controversy over the formation mechanisms and material sources of these volcanoes. The mantle transition zone (MTZ), as a necessary channel for the upward and downward movement of mantle material and energy exchange may provide crucial constraints on the dynamic mechanisms of volcanic activity. This paper intends to obtain the deep structure beneath the eastern CAOB based on the geomagnetic depth sounding (GDS) method. First, the data of geomagnetic observatories in the study region are collected and processed, and the C -response curves are obtained by the bounded influence remote reference processing method (BIRRP). Then, the staggered grid finite difference method is used for forward modeling, and the finite memory quasi-Newton method based on L 1 -norm is used for three-dimensional (3-D) inversion. After that, 3-D inversion is carried out in spherical coordinates. Finally, the electrical conductivity model is obtained. The inversion model shows that there are two high conductivity anomalies in the MTZ beneath the Mongol-Okhotsk suture. Combined with the geological background of the structural domain, and constrained by the spatiotemporal variations in magmatism, we speculate that the high conductivity anomaly bodies are the stagnant oceanic crust material of the Okhotsk Ocean or the delaminated island arc accretionary wedge. The sinking slab or the detached lithosphere residual descending into the lower MTZ causes the upwelling of hot mantle material, forming widely distributed volcanic rocks on both sides of the Mongol-Okhotsk suture.